GC-MS PHYTOCHEMICAL ANALYSIS AND COMPARATIVE PHOTOCATALYTIC DEGRADATION PROCEDURE BETWEEN ZNO AND SB2O3 IN EXTRACT OF LEAF GYNANDRIRIS SISYRINCHIUM (L.) PARL. - Altameme, Huda J. M.; Al-gubury, H Y.; Ismeel, M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present research was conducted to the Gynandris sisyrinchium (L.) Parl. leaves extract to identify the phytochemicals present and determine the qualitative presence of phenols and flavonoids. The GC-MS findings have different peaks to determine the existence of 23 phytochemical compounds which may have a role in pharmacological activities. On another side, A photocatalytic degradation of extracted dye using ZnO and Sb2O3 was tested, which is done by the photodegrade of a suspended aqueous solution of extracted dye with 0.17gm/100ml of semiconductor starting with ZnO then Sb2O3 under UV lamp (125 Watts) at 298 K. To reach the best photodegradation several experiments have been carried out. Started by the effect on the photocatalytic degradation of the extracted colorant of the semiconductor and the effect of the dye concentration extracted. Using UV-Vis spectrophotometer, the products were tested. It can be noted, from all experiments, that the employing of zinc oxide as a photocatalyst was found to be more effective than Sb2O3 to degradation of dye.